Pendampingan Penyusunan Laporan Keuangan Bumdes Munte - Mukhammad Idrus; Warka Syachbrani (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. This program aims to ensure the preparation of financial statements of Village-Owned Enterprises (Bumdes) in accordance with general acceoted financial accounting standards. This Community Partnership Program (PKM) is implemented in Munte Village, North Luwu. Activity partners for the management and employees of Bumdes. Partner problems are: (1) limited knowledge and skills in preparing financial reports, (2) limited human resources owned by partners, and (3) the need to prepare and report financial transactions in accordance with Government regulations. External targets are the management and employees of Village-Owned Enterprises who are able to compile financial reports in accordance with applicable accounting standards. The methods used are: lectures, demonstrations, discussions, questions and answers, and partner assistance. The results achieved are (1) partners have basic knowledge in analyzing and recording financial transactions that occur in their business entities, (2) partners have the skills to compile Bumdes financial reports in accordance with applicable accounting standards, and (3) partners have the ability to organize the bookkeeping of business entities so that they have quality information.